2011
DOI: 10.1080/15374416.2011.563472
|View full text |Cite
|
Sign up to set email alerts
|

International Comparisons of Behavioral and Emotional Problems in Preschool Children: Parents' Reports From 24 Societies

Abstract: International comparisons were conducted of preschool children’s behavioral and emotional problems as reported on the Child Behavior Checklist for Ages 1½–5 by parents in 24 societies (N =19,850). Item ratings were aggregated into scores on syndromes; Diagnostic and Statistical Manual of Mental Disorders–oriented scales; a Stress Problems scale; and Internalizing, Externalizing, and Total Problems scales. Effect sizes for scale score differences among the 24 societies ranged from small to medium (3–12%). Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
133
2
20

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 187 publications
(169 citation statements)
references
References 25 publications
(27 reference statements)
14
133
2
20
Order By: Relevance
“…Recall that 5-HTTLPR s/s homozygotes displayed (1) the most attention problems and hyperactivity when exposed to high levels of intrusive care, but (2) the least ADHD symptoms, with a mean score similar to the general population [59], when exposed to low levels of such care; and (3) there was no detectable effect of caregiving intrusiveness in the case of l-allele carriers. The pattern of GXE interaction detected in this inquiry is consistent with a differential-susceptibility framework of person × environment interaction, rather than with the diathesis-stress model.…”
Section: Discussionmentioning
confidence: 99%
“…Recall that 5-HTTLPR s/s homozygotes displayed (1) the most attention problems and hyperactivity when exposed to high levels of intrusive care, but (2) the least ADHD symptoms, with a mean score similar to the general population [59], when exposed to low levels of such care; and (3) there was no detectable effect of caregiving intrusiveness in the case of l-allele carriers. The pattern of GXE interaction detected in this inquiry is consistent with a differential-susceptibility framework of person × environment interaction, rather than with the diathesis-stress model.…”
Section: Discussionmentioning
confidence: 99%
“…32 The CBCL is one of the questionnaires most frequently used to assess behavior problems in a range of cultures, and is designed to be completed by parents or those who interact with the child at home. 17,33 In Brazil, it has been used in epidemiologic studies and to measure treatment effects. 16,34 We used the 1991 version of the CBCL to investigate behavior problems in our sample.…”
Section: Child Behavior Checklist (Cbcl)mentioning
confidence: 99%
“…An international study using the CBCL with children aged 17 to 60 months compared 19,850 children from 24 societies in developed and developing countries. 17 The authors reported the average prevalence of behavior problems to account for 33.3% of total problems within this age group.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizando o CBCL, um estudo multicultural de alta relevância realizado em 31 países situados nos continentes Americano, Asiático, Europeu e Oceania (Rescorla et al, 2011) sinalizou inconsistência nas sociedades analisadas cujos resultados variaram em função da idade, como, por exemplo, na maioria dos países, o gênero feminino de 12 a 16 anos, apresentou escores mais elevados nos comportamentos internalizantes, ou seja, as meninas de 6 a 11 anos não apontaram diferença significativa. Já os meninos 6 a 11 anos alcançaram escores mais elevados nos comportamentos externalizantes, mas isso não se aplicou em todas as sociedades.…”
Section: Escala De Internalizaçãounclassified
“…Já os externalizantes, são comportamentos dirigidos ao meio externo, evidenciados por oposição, condutas desafiadoras excessivas, manifestações antissociais, agressão física ou verbal, hostilidade, conduta disruptiva, impulsividade, uso de substâncias, entre outros sintomas (American Psychiatric Association, 2013;Archenbach & Edelbrock, 1983;Rescorla et al, 2011).…”
unclassified